End-of-Life Issues in adults - Euthanasia - Vasileiadis, Georgios; Zacharopoulos, Dimitrios; Kousi, Chrisaugi; Tzermpinou, Anthi (Bioethica, 2022)
This paper was prepared in the framework of the educational Seminars on “Contemporary Issues of Bioethics” – 4th Cycle (February – May 2021) organized by the Hellenic National Commission for Bioethics and Technoethics and the Laboratory for the Research of Medical law and Bioethics of A.U.Th. School of Law. The subject of the study is the end-of-life issues in adults and euthanasia, a long-standing issue that affects the thinking of scientists from different fields of science. For this reason we collaborated scientists from different fields trying to analyze how each field of science deals with issues related to the end of life and euthanasia. Precisely, the aim of the study is to analyze and highlight thoroughly and comprehensively these issues in order to present some concluding remarks. First, are analyzed the ethical issues raised about euthanasia and in general the end of the life, followed by the position of the various religions on the end-of-life issues. Then, an attempt is made to find the existence or not of a right to die, the legal delimitation and regulation of the above referred issues with emphasis on euthanasia and to analyze the case law, mainly the decisions of the European Court of Human Rights (ECHR). Finally, the present study clarifies and addresses the way in which the forensic science deals with the end-of-life issues.